Against postmodernism: Paolo Sorrentino and the search for authenticity - Cangiano, Mimmo (Journal of Italian Cinema & Media Studies, 2019)
The concept of identity lies at the heart of every one of Paolo Sorrentino’s movies. His main characters are engaged in a struggle to define themselves since through this alone can they hope to overcome the futility and inconsistency of their lives. Sorrentino’s cinematic oeuvre thus challenges postmodernist theories on identity. In his movies, the absence of an identity does not imply the liberation of the subject from the constraints of social roles, but instead relegates her/him to a life deprived of any value and a reality that is completely superficial and unworthy. Therefore, for Sorrentino, seeking an identity means seeking a way to interpret reality. This article will show how the Neapolitan director has focused his entire work around this Romantic and modernist topic: the search for authenticity and the subject’s ability to produce value only after discovering an authentic Self.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qaWNtcy43LjMuMzM5XzE